Means of innovative pedagogical technologies in preparation of future teachers of physical culture - Sukhobok O. Y. (Kharkov National Pedagogical University, 2011)
The problem of introduction of facilities of innovative pedagogical technologies is analysed in professionally methodical preparation of future teachers of physical culture. Basis of innovative processes in education is made: problem of study, generalization and distribution of front-rank pedagogical experience. Also problem of introduction of achievements to pedagogical sciences in practice was considered. The most perspective directions and methods of the use of innovative pedagogical technologies are considered. They positively influence on forming of methodical competence of future teachers. Among directions it is selected module-developing teaching, facilities informatively of communication technologies, method of projects. It is marked that the personality oriented pedagogical technologies provide professional and social mobility of future specialist, his competitiveness at the market of labour.